19 Quality Improvement bundled approach reduces the use of inotropes in extremely premature babies. (21st October 2022) - Venkata, Sujith Kumar Reddy Gurram; Srivastava, Ankur; Murthy, Prashanth; Scott, James; Zein, Hussein; Leijser, Lara; Ghosh, Anirban; Momin, Sarfaraz; Thomas, Sumesh; Mohammad, Khorshid
Abstract: Background: Consensus on definition and management of hypotension in preterm neonates is lacking. Owing to this, there are wide variations in the reported incidence of hypotension in premature infants, especially during first week of life. Inotropes can often cause vasoconstriction, which may alter brain perfusion especially in the absence of established cerebral autoregulation. Use of these drugs is associated with multiple short- and long-term morbidities. Objectives: To evaluate the effect of quality improvement (QI) bundle on rate of inotrope use and associated morbidities. Design/Methods: Inborn preterm neonates born at <29weeks gestational age (GA) and admitted to level III NICU were included. Neonates with major congenital malformations, congenital heart diseases, antenatal diagnosed genetic defects, and neonates admitted after 72 hours of age were excluded from the study. We implemented a QI bundle (Figure 1) focussing on first 72hours from birth which included delayed cord clamping, avoidance of routine echocardiography, addition of clinical criteria to define hypotension, factoring iatrogenic causes of hypotension (ruling out lung hyperinflation), and standardization of respiratory management. Rate of use of inotropes in the first 72hours of life along with acute brain injury and mortality before and after implementation of the QI bundle were compared. The balancing measure was the rate of ischemic lesions in the form of cPVL. Cranial ultrasound was performed to screen for brain injury. Study was approved by the local research ethics board (REB14-1466 ). Results: We included 671 neonates (301 before and 364 after the implementation of the bundle) among which 6 neonates were excluded based on the criteria. QI bundle implementation was associated with significant reduction in overall use of inotropes (24% vs 7%, p<0.001), dopamine (18% vs 5%, p<0.001), and dobutamine (17% vs 4%, p<0.001). Rate of acute brain injury decreased significantly: Acute brain injury of any grade (34% vs 20%, p<0.001) and severe brain injury (15% vs 6%, p<0.001). There was no difference in incidence of cPVL (1% vs 1.4%, p=0.66). Associations remained significant after adjusting for confounding factors. The QI bundle implementation was associated with a significant reduction in the use of inotropes when analyzed based on the 6 monthly time intervals (p = 0.006) (Figure 2) Conclusion: Our QI bundled approach resulted in reduction in inotrope use and associated brain morbidities in premature babies. Follow-up studies evaluating the impact of this initiative on long-term outcomes in survivors are required to complement findings of improved short-term outcomes seen in this study.